Effect of chemically and biologically treated rice straw on some productive characteristics of Iraqi buffalo (Bubalus bubalis) calves - Ibrahim, Ali Jalil; Al-Samaraae, Wafaa Hameed.; Ajil, Hmood M. (Journal of Kerbala for Agricultural Sciences, 2022)
This study was conducted to find out the effect of chemically treating rice straw with urea and biologically with the fungus Trichoderma harzianum on feeding Iraqi buffalo calves on the weight gain, feed intake, and feed conversion. The results showed that there were highly significant differences (P<0.01) between treatments in the amount of total feed intake, as T2 (7.713 kg) and T3 (7.428 g) were compared with T1 (6.461 kg), and in the amount of nutrients intake for roughage, where T3 was significantly superior (P<0.05) on T1 intake from daily roughage 2804.2, 2191.7 gm for T3 and T1, respectively, while T2 did not differ significantly from T1 and T3. The results showed significant differences in the intake of nutrients from roughage, where T3 and T2 were significantly (P<0.01) superior to T1 in crude protein, ether extract, ash, and metabolic energy, and the differences were significant (P<0.05) in favor of T2 and T3 in both dry matters. organic matter and nitrogen-free extract. The treatments had a highly significant effect on the intake of total roughage, and significantly (P<0.01) T3 and T1 in dry matter, organic matter, crude protein, nitrogen-free extract, and metabolic energy, while the treatments did not significantly effect crude fiber. The results also showed that treatment with urea and fungi led to a highly significant increase (P<0.01) in the weight gain (daily and total) and a high improvement in the feed conversion ratio for calves. We conclude that the chemical (Urea) and biological (T. harzianum) straw treatment led to an improvement in the nutritional value of the rice straw by raising the nitrogen content in it and improving the feed conversion ratio, knowing that the effect of the biological treatment was significantly better.